Analisis Faktor-Faktor Yang Mempengaruhi Postpartum Blues Pada Masa COVID-19 di Kabupaten Semarang - Dewi Mayangsari; Eni Kusyati; Hastika Ulfatu Nikhmah (PROFESSIONAL HEALTH JOURNAL, 2023)
Abstract Background:Coronavirus Disease 2019 (COVID-19) is a viral disease that is endemic almost throughout the world due to SARSCOV-2. The existence of a pandemic causes anxiety in pregnant and postpartum women, and risks occurringpostpartum blues. Incidence ratepostpartum blues in Indonesia it is still high, namely 37% -67%.Research methods:Quantitative, designcross sectional, research subjects were 41 respondents in motherspostpartum 3rd day with techniquepurposive sampling, questionnaires usingEdinburgh Postnatal Depression Scale (EPDS) and social support questionnaire usePostpartum Depression Predictors Inventory (PDPI). Analysis of the data used in the testchi-square.Research result:Postpartum most people experience itpostpartum blues; unhealthy reproductive age, namely 10 respondents (76.9%), type of surgical/SC delivery, namely 16 respondents (51.2%), junior/high school education level, namely 10 respondents (52.6%), not working, namely 15 respondents ( 65.2%) and did not receive social support, namely 11 respondents (73.3%). Age withp-value 0.034 (OR 6.0; 95% CI 1.33-26.9), type of delivery withp-value 0.034 (OR 5.3; 95% CI 1.32-21.53), jobs withp-value 0.039 (OR 0.2; 95% CI 0.54-0.78), social support withp-value 0.039 (OR 0.19; 95% CI 0.047-0.781), education withp-value 0,807. Conclusions Discussion/Suggestion: Event-related variablespostpartum blues during Covid-19, namely; age, type of delivery, employment, and social support. Maternal screeningpostpartum blues can be implemented with the EPDS questionnaire as a procedure and provide counseling. Keywords: Social Support, Type of Childbirth, Age, Education, Occupation,Postpartum Blues Latar Belakang: Coronavirus Disease 2019 (COVID-19) adalah penyakit virus yang sedang mewabah hampir seluruh dunia akibat SARSCOV-2. Adanya pandemi menyebabkan kecemasan pada ibu hamil dan nifas, dan berisiko terjadi postpartum blues. Angka kejadian postpartum blues di Indonesia masih tinggi, yaitu 37%-67%. Metode Penelitian: Kuantitatif, desain cross sectional, subjek penelitian 41 responden pada ibu postpartum hari ke-3 dengan teknik purposive sampling, kuesioner menggunakan Edinburgh Postnatal Depression Scale (EPDS) dan kuesioner dukungan sosial menggunakan Postpartum Depression Predictors Inventory (PDPI). Analisis data yang digunakan uji chi-square. Hasil Penelitian: Postpartum terbanyak yang mengalami postpartum blues; usia reproduksi tidak sehat yaitu 10 responden (76,9%), jenis persalinan tindakan/SC yaitu 16 responden (51,2%), tingkat pendidikan SMP/SLTA yaitu 10 responden (52,6%), tidak bekerja yaitu 15 responden (65,2%) dan tidak mendapat dukungan sosial yaitu 11 responden (73,3%). Usia dengan p-value 0,034 (OR 6,0 ; 95% CI 1,33-26,9), jenis persalinan dengan p-value 0,034 (OR 5,3 ; 95% CI 1,32-21,53), pekerjaan dengan p-value 0,039 (OR 0,2 ; 95% CI 0,54-0,78), dukungan sosial dengan p-value 0,039 (OR 0,19 ; 95% CI 0,047-0,781), pendidikan dengan p-value 0,807. Kesimpulan dan saran: Variabel yang berhubungan dengan kejadian postpartum blues pada masa covid-19 yaitu; usia, jenis persalinan, pekerjaan, dan dukungan sosial. Skrining ibu postpartum blues bisa diterapkan dengan kuesioner EPDS menjadi protap dan memberikan konseling. Kata kunci: Dukungan Sosial, Jenis Persalinan, Usia, Pendidikan, Pekerjaan, Postpartum Blues